Hypoxia inducible factor 2α (HIF2α/EPAS1) is associated with development of pulmonary hypertension in severe congenital diaphragmatic hernia patients. (June 2018) - Huang, Yadi; Boerema-de Munck, Anne; Buscop-van Kempen, Marjon; Sluiter, Ilona; de Krijger, Ronald; Tibboel, Dick; Rottier, Robbert J.
We show that hypoxia inducible factor 2α (HIF2α) is highly expressed in patients with pulmonary hypertension (PH). HIF2α is expressed in every patient with congenital diaphragmatic hernia, while only half of the controls express HIF2α. Our data suggest that HIF2α is a link between hypoxia and the development of PH.